MATERIALISM VERSUS POST-MATERIALISM, POLITICAL PARTICIPATION AND ATTITUDES TOWARDS DEMOCRACY: AN EMPIRICAL EXAMINATION OF TOCQUEVILLE’S IDEA - Yongbo Liu; Shen Lihe (Journal of Social Political Sciences, 2022)
Tocqueville suggested that materialism may result in a lower level of political participation and lower support for democracy. In this study, using the joint dataset of the World Values Survey (WVS) and the European Values Study (EVS) 2017-2020, we examine the influence of materialism/post-materialism on people’s support for democracy. From a hierarchical linear model, our results indicate that materialism against post-materialism is associated with a lower level of support for democracy, which supports Tocqueville’s theory. Furthermore, using causal mediation analysis, we find that political participation mediates 9.92% of the effect of materialism/post-materialism on support for democracy. Our results show that materialism/post-materialism is an important determinant to people’s support for democracy. Political participation is an important mechanism for the association between materialism/post-materialism and support for democracy.